The Influence of the Visualization, Auditory, Kinesthetic (VAK) Learning Model Assisted by Song Clip Video Media on the Poetry Writing Ability of Class X Students of SMA Negeri 7 Medan - Annisa Aulia Rahmadani; Rosmaini (Indonesian Journal of Advanced Research, 2024)
This research aims to determine the effect of the Visualization, Auditory, Kinesthetic (VAK) learning model assisted by Song Clip Video Media on the Poetry Writing Ability of Class X Students of SMA Negeri 7 Medan in the 2023/2024 Academic Year. The research method used is the experimental two group post-test design method. The research results showed that the average score for the poetry writing ability of experimental class students was 79.68, which was considered good, while the average score for the control class was 62.88, which was considered sufficient. Hypothesis testing shows that tcount > ttable, namely, 6.17 > 2.056, so the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is an influence of the Visualization, Auditory, Kinesthetic (VAK) learning model assisted by song video clip media on the ability to write poetry in class X students of SMA Negeri 7 Medan for the 2023/2024 academic year.